290 THE VARIABLE INDICATIVE OF PLACEMENT IN ACUTE HOSPITAL OUTPATIENT CLINICS IDENTIFIES OLDER ADULTS WHO BENEFIT FROM SPECIALIST GERIATRIC ASSESSMENT. (25th October 2022) - Maher, J; McKenna-Barry, M; Donnellan, C; Pillay, I
Abstract: Background: Opportunistic screening of older adults results in early detection of frailty. The Variable Indicative of Placement (VIP) is validated to identify those being admitted to hospital who may benefit from specialist geriatric assessment. VIP screening was gradually introduced throughout hospital-based outpatient clinics in April 2021. The aim of this study was to quantify patient benefit following VIP screening. Methods: A positive VIP triggered referral for Comprehensive Geriatric Assessment (CGA). Exclusion criteria included prior CGA within a year, nursing home resident or patient declined assessment. Data was prospectively entered onto Excel by a trained administrator. Demographics, Clinical Frailty Score (CFS), modified Barthel Index (mBI) and patient interventions post CGA, between July 2021 and April 2022, were analysed using descriptive statistics. Results: Of 168 referrals received, 52 were excluded, 53 completed and 63 await review. Thirty-five of those excluded had a prior CGA. Mean (SD) age of patients receiving CGA was 79 (7.6) years. Male:female ratio was 1:1.4. Median (SD) CFS was 6 (0.8) and median (SD) mBI was 16(3.9). There was a mean (SD) of 2.8 (1.6) targeted interventions per patient. Eighty three percent (n=43) required medication changes, 47% (n=25) bone health management, 28% (n=15) dietician, 26% (n=14) occupational therapy, 17% (n=9) public health nursing, 17% (n=9) speech and language therapy, 17% (n=9) memory assessment and 15% (n=8) physiotherapy. Conclusion: Outpatient clinic VIP screening resulted in identification of frail older adults who benefited from CGA. The VIP should be validated in various outpatient settings.